Molecular characterization of Phytophthora palmivora Butler and evaluation of Morinda citrifolia L. leaf extract for controlling stem canker on durian - Nor Danial, Nor Dalila (2023)
Commercial durian production in Malaysia has doubled in the last decade and durian growers are receiving premium price from their fruits from local and international consumers. Stem canker, caused by Phytophthora palmivora is a major problem for durian farmers in Malaysia, but limited studies addressed their genetic diversity using multiple genes. Therefore, this study was conducted to characterize Phytophthora species from main durian orchards infected by stem canker in Malaysia using morphological, sequence analyses of the internal transcribed spacer (ITS) regions of ribosomal deoxyribonucleic acid (rDNA) and cytochrome oxidase c (COX) regions. Fungicides containing metalaxyl and phosphonate have been long used for this disease management in durian fields. However, the repeated and extensive use of similar fungicide developed resistant Phytophthora isolates. Research into new approaches of managing such pathogens are of importance. Morinda citrifolia, a medicinally valued plant that are commonly found in Malaysia can be a beneficial complement to chemical fungicides. This study was also to identify the compounds of M. citrifolia leaf crude extracts extracted using methanol, acetone, ethyl acetate and hexane. In addition, this study was carried out to evaluate in vitro and in vivo efficacy of M. citrifolia leaf crude extracts against the mycelial growth of P. palmivora. A total of 21 Phytophthora isolates were obtained from water-soaked lesions of durian stem tissues collected from 4 different states of Malaysia in 2019, Selangor (n=10), Perak (n=4), Pahang (n=4) and Melaka (n=3). All isolates had morphological characteristics similar to that of P. palmivora. For molecular identification, the results of BLASTn using the ITS and COX sequences identified them as P. palmivora with 99-100% with P. palmivora culture (GenBank accession no. ON834450 for the ITS region and JF771543 for the Cox region). Results of phylogenetic analyses of the ITS rDNA and COX confirmed that all Phytophthora isolates belonged to P. palmivora and clustered into one clade with reference P. palmivora isolates, supported by high bootstrap values for the ITS (100%) and COX (76%) regions. Pathogenicity tests showed all isolates were pathogenic on durian leaves, where PMM02 had significantly the lowest virulence among all isolates with a lesion diameter of 64.04 mm at day 8. The detached leaf assays using durian leaves of D10, D24 and Mousang King varieties showed there was significance among durian varieties, where D10 was proven to be more susceptible towards P. palmivora. GC-MS analysis of M. citrifolia leaves crude extract revealed the presence of squalene. In vitro evaluation of M. citrifolia crude extracts acetone and ethyl acetate showed an effective concentration 50% (EC50) values of 36.12 mg/mL and 38.10 mg/mL, respectively. Plate treated with acetone solvent at 60 mg/mL altered the morphology and inhibit the mycelial growth of P. palmivora at microscopic observation using scanning electron microscope. In vivo bioassay evaluation, plants treated with M. citrifolia extract of ethyl acetate 76 mg/mL had a lesion growth of 30.24 mm on the stem. This treatment was not significantly difference to control positive treatment applied with Ridomil fungicide. M. citrifolia methanol, acetone and ethyl acetate contain antifungal compounds and can be used as biofungicides for stem canker disease management.